Short- and long-term mortality in patients with type 2 diabetes after myocardial infarction- a nationwide registry study - Kerola, Anne M.; Juonala, Markus; Kytö, Ville (BMC, 2025)
Background Type 2 diabetes has traditionally been a risk factor for worse prognosis after myocardial infarction (MI), but major advances have been made in its treatment, and the use of secondary preventive measures has intensified. We evaluated the short- and long-term mortality rates of patients with type 2 diabetes after MI and explored the associations between the characteristics of patients with type 2 diabetes and MI mortality.
Methods Mortality rates among consecutive MI patients with type 2 diabetes using oral antidiabetic medication (n = 13,152; 40% female; mean age 73.6 years) and MI patients without diabetes (n = 77,669) treated in Finland from 2004 to 2018 were retrospectively studied using a combination of national registries (median follow-up 5.7 years). Differences between groups were balanced with multivariable adjustments and propensity score matching.
Results Mortality was higher in patients with type 2 diabetes than in the propensity score-matched controls without diabetes at 30 days (12.6% versus 12.0%: p = 0.013), at 1 year (22.4% versus 21.4%; p = 0.001), and at 15 years (83.2% vs. 73.4%; HR 1.20; 95% CI 1.17-1.24; p < 0.0001) after MI. In subgroup analyses, type 2 diabetes was associated with a poorer prognosis across the spectrum of MI patients. The excess mortality risk was attenuated by increasing age but was similar in both sexes. Male sex, age, cardiovascular and noncardiovascular co-morbidities, lack of revascularization, a longer duration of diabetes, and baseline insulin therapy were associated with increased mortality in patients with type 2 diabetes. The one-year prognosis of patients with type 2 diabetes improved during the study period, but the mortality gap compared to patients without diabetes was not altered.
Conclusions Type 2 diabetes had a negative impact on both short- and long-term outcome after MI, but effect sizes were relatively small. Patients with longer duration of diabetes or need for insulin therapy are still at particular risk.